Sabella : or, The blood stone - Lee, Tanith (DAW book collectors, 2020)
Struggling to hide her true nature, Sabella, a vampire who has sworn off of drinking human blood, must keep her identity safe from a private investigator who is determined to expose her for what she is despite being enthralled by her charms.